Coal rapid pyrolysis in a transport bed under steam-containing syngas atmosphere relevant to the integrated fluidized bed gasification. (15th July 2016) - Chen, Zhaohui; Shi, Yong; Lai, Dengguo; Gao, Shiqiu; Shi, Zhen; Tian, Yong; Xu, Guangwen
Highlights: A transport bed was used to study the effect of steam-containing syngas on coal rapid pyrolysis. Steam-containing syngas combined the advantages of steam and syngas on tar production. Steam-containing syngas atmosphere was beneficial to CH4 production. Abstract: An integrated fluidized bed (IFB) consisting of an upper transport bed section and a bottom fluidized bed section was adopted to investigate the transport bed coal pyrolysis by varying its reaction temperature and reaction atmosphere adjusted to simulate steam-containing syngas produced by the bottom fluidized bed char gasification. Steam and syngas, in comparison with N2, as the reaction atmosphere little affected the tar yield below 600 °C but significantly decreased it for the former and increased it for the latter at rather higher temperatures. The presence of H2 in the syngas increased tar yield significantly because it could suppress polymerization and condensation reactions through providing H as radical stabilizer and hydrogenation agent. In the steam-containing syngas atmosphere, the tar yield obtained from transport bed rapid pyrolysis increased rapidly with raising temperature to a peak value of 10.5 wt.% (daf) at 600 °C, about 1.1 wt.% higher than the Gray–King assay yield, and then decreased due to the excessive secondary reactions. Analyzing tar composition further showed that steam-containing syngas combined their respective advantages that syngas improved the yields of both light and heavy tars while steam reduced the heavy tar yield, especially at temperatures above 600 °C. The steam-containing syngas atmosphere also promoted CH4 production in comparison with syngas atmosphere below 700 °C.